Symmetry-dependent interfacial reconstruction to compensate polar discontinuity at perovskite oxide interfaces (LaAlO3/SrTiO3 and LaAlO3/CaTiO3) - Lee, Joohwi; Choi, Jong Kwon; Moon, Seon Young; Park, Jaehong; Kim, Jin-Sang; Hwang, Cheol Seong; Baek, Seung-Hyub; Choi, Jung-Hae; Chang, Hye Jung (AMER INST PHYSICS, 2015)
We report the crystal symmetry-dependency of the interfacial reconstruction to relieve the polar discontinuity at the complex oxide heterointerfaces. We chose LaAlO3/SrTiO3 and LaAlO3/CaTiO3 interfaces as model systems, where the neutral TiO2 and the positive LaO+ layers form the polar discontinuity at the interface with TiO2-terminated (001) cubic SrTiO3 and orthorhombic CaTiO3. Using scanning transmission electron microscopy, we observed that the interlayer distance abnormally increased at the interface. We performed the first-principles calculations to understand the detailed atomic displacement at the interfaces having no oxygen vacancy and intermixing. Our results show that cations were reconstructed in different ways depending on the crystal symmetry through the octahedral tilts and atomic displacements to compensate the polar discontinuity at the interfaces. Our results imply that the interfacial reconstructions have to be considered along with the ionic compensation (intermixing) and electronic compensation (two dimensional electron gas) to fully understand the interfacial phenomena. (C) 2015 AIP Publishing LLC.
Keywords: SRTIO3/LAALO3 INTERFACES; MAGNETIC-PROPERTIES; EPITAXIAL STRAIN; ELECTRIC-FIELDS; THIN-FILMS; SURFACE; SRTIO3; SRRUO3; GAS